Estrogen-mediated downregulation of HIF-1 alpha signaling in B lymphocytes influences postmenopausal bone loss - Meng, Xianyi; Lin, Zhen; Cao, Shan; Janowska, Iga; Sonomoto, Koshiro; Andreev, Darja; Knab, Katharina; Wen, Jinming; Knaup, Karl; Krönke, Gerhard; Rizzi, Marta; Schett, Georg; et al. (Bone Research, 2022)
In the bone marrow, B cells and bone-resorbing osteoclasts colocalize and form a specific microenvironment. How B cells functionally influence osteoclasts and bone architecture is poorly understood. Using genetically modified mice and high-throughput analyses, we demonstrate that prolonged HIF-1 alpha signaling in B cells leads to enhanced RANKL production and osteoclast formation. In addition, deletion of HIF-1 alpha in B cells prevents estrogen deficiency-induced bone loss in mice. Mechanistically, estrogen controls HIF-1 alpha protein stabilization through HSP70-mediated degradation in bone marrow B cells. The stabilization of HIF-1 alpha protein in HSP70-deficient bone marrow B cells promotes RANKL production and osteoclastogenesis. Induction of HSP70 expression by geranylgeranylacetone (GGA) administration alleviates ovariectomy-induced osteoporosis. Moreover, RANKL gene expression has a positive correlation with HIF1A expression in human B cells. In conclusion, HIF-1 alpha signaling in B cells is crucial for the control of osteoclastogenesis, and the HSP70/HIF-1 alpha axis may serve as a new therapeutic target for osteoporosis.
CRIS-Team WoS Importer:2022-03-04